Cervical Cancer Stigma Among Caribbean Population: A Descriptive Paper - Kamilah Thomas-Purcell; Althea Bailey; Diadrey-Anne Sealy; Gaole Song; Kimlin Tam Ashing (Frontiers Media S.A., 2024)
Objectives: Cervical cancer prevention practices are desperately low in the Caribbean. This study aims to describe the cervical cancer stigma and to evaluate the influence of the prevention practices among the Caribbean non-patient population in Jamaica, Grenada, Trinidad and Tobago.Methods: A cross-sectional study involving 1,207 participants was conducted using a culturally trans-created Cancer Stigma Scale for the Caribbean context and supplemented with questions on cervical cancer and HPV/HPV vaccine knowledge and beliefs. Data collection took place online from October 2022 to March 2023.Results: Participants are young, single, well-educated, and have stable financial resources. Over a quarter (26.4%) agreed women with cervical cancer are more isolated in their country. Almost half (47%) of respondents agreed cultural background plays a big part in how they feel about illness and getting well. One in six participants believe women with cervical cancer are treated with less respect than usual by others in their country.Conclusion: Cancer stigma of cervical cancer exists in Jamaica, Trinidad and Tobago, and Grenada. Particularly, cultural background and social norms are closely linked to stigma.